Conformational implications of enzymatic proline hydroxylation in collagen. - Chopra, R K (1982)
In 1979 it was proposed that prolyl hydroxylase (prolyl-glycyl-peptide,2-oxoglutarate:oxygen oxidoreductase, EC 1.14.11.2) recognizes the beta-turn conformation in nascent procollagen chains and that the hydroxylation process involves a conformational change resulting in "straightening" of the beta-turn segments into the linear triple-helical conformation of native collagen. We present experimental data that verify both these postulates. The following peptides were synthesized and studied for their conformation and interaction with prolyl hydroxylase: tBoc-Pro-Gly-Ala-OH, tBoc-Pro-Gly-Val-OH, tBoc-Gly-Val-Pro-Gly-Val-OH, and tBoc-Pro-DAla-Ala-OH. Spectral data showed that these peptides preferred a beta-turn conformation. All of them acted as inhibitors of the enzyme; the pentapeptide also acted as a substrate. To mimic the biosynthetic event, a collagen model polypeptide, (Pro-Pro-Gly)10, was incubated at 37 degrees C with purified prolyl hydroxylase and the necessary cosubstrates and cofactors at pH 7.8. A progressive change from the initially nonhelical to the triple-helical conformation, as monitored by CD spectra and gel filtration, occurred during the course of proline hydroxylation. In addition to leading to increased thermal stability of the triple-helical conformation in (Pro-Pro-Gly)10 and (Pro-Pro-Gly)5, the enzymatic incorporation of the hydroxyproline residues was found to enable these polypeptides to fold into this conformation faster than the unhydroxylated counterparts. These conformational implications of proline hydroxylation in collagen may also be of use in the study of the complement subcomponent Clq and of acetylcholine esterase which contain collagen-like regions in them.